Antenatal magnesium sulfate to prevent cerebral palsy. Issue 2 (7th July 2021) - Keir, Amy K; Shepherd, Emily; McIntyre, Sarah; Rumbold, Alice; Groves, Charlotte; Crowther, Caroline; Callander, Emily Joy
Abstract : Magnesium sulfate given to women before birth at <30 weeks' gestation reduces the risk of cerebral palsy in their children. Our study aimed to assess the impact of a local quality improvement programme, primarily using plan-do-study-act cycles, to increase the use of antenatal magnesium sulfate. After implementing our quality improvement programme, an average of 86% of babies delivered at <30 weeks' gestation were exposed to antenatal magnesium sulfate compared with a historical baseline rate of 63%. Our study strengthens the case for embedding quality improvement programmes in maternal perinatal care to reduce the impact of cerebral palsy on families and society. Abstract : Embedding a quality improvement program on prenatal magnesium administration is feasible to reduce the impact of cerebral palsy.